Design of Effective Liquefaction Unit in LNG Plant Process based on Economic Study - Eky Novianarenti; Erlinda Ningsih; Heroe Poernomo; Imaniah Sriwijayasih; Arrad Ghani S; Rizal Mahmud; Abdul Kadir Djaelani (International Conference on Maritime Technology and Its Application, 2024)
Liquified Natural Gas (LNG) is natural gas that is used as a safe, clean and efficient energy source. LNG itself is liquefied and has been processed to remove impurities and heavy fraction hydrocarbons which are then condensed into liquid at atmospheric pressure with a temperature of -160 ºC. In Indonesia, LNG has good prospects for development, both in terms of raw material potential and its market. So, it is very appropriate if an LNG plant is established in Indonesia with the aim of meeting domestic LNG needs and opening up new jobs to reduce unemployment in Indonesia. LNG is made through several stages of the process, namely the Absorption, Dehydration, Fractionation and Liquefaction processes. The factory will be established in Muara Enim, Lahan Regency, South Sumatra Province. From economic calculations, it is obtained that the return on investment is 3.08 years after the factory is established. The rate of return on capital is 38.1%, and the BEP is 37.6%. Based on the economic analysis, the LNG plant from Natural Gas is feasible to be established.